Laplace's Demon and the Adventures of His Apprentices. Issue 1 (January 2014) - Frigg, Roman; Bradley, Seamus; Du, Hailiang; Smith, Leonard A.
Abstract : The sensitive dependence on initial conditions (SDIC) associated with nonlinear models imposes limitations on the models' predictive power. We draw attention to an additional limitation than has been underappreciated, namely, structural model error (SME). A model has SME if the model dynamics differ from the dynamics in the target system. If a nonlinear model has only the slightest SME, then its ability to generate decision-relevant predictions is compromised. Given a perfect model, we can take the effects of SDIC into account by substituting probabilistic predictions for point predictions. This route is foreclosed in the case of SME, which puts us in a worse epistemic situation than SDIC.